Management of Closed Pyometra-induced Acute Kidney Injury by Intermitent Hemodialysis in a Labrador Retriever Dog - Randhir Singh; Sachin; Gurpreet Singh Preet; Ramanpreet Singh; Rajsukhbir Singh; Vinay Yadav; Bilawal Singh (Archives of Current Research International, 2025)
Aims: This case report underscores the importance of intermittent hemodialysis (IHD) for treatment of closed pyometra induced AKI in dog. Presentation of Case: A 9-year-old female Labrador retriever dog with history of inappetence, lethargy, intermittent vomiting, melena, polyuria and polydipsia was presented to Multispecialty Hospital, Guru Angad Dev Veterinary and Animal Sciences University, Ludhiana. Initial physical assessment revealed body condition score- 3, congested mucus membrane, with normal vital parameters. Complete blood counts revealed neutrophilic leukocytosis and severe left shift. Biochemistry revealed derailed renal function values [Blood urea nitrogen (BUN)- 93 mg/dl, Creatinine- 9.7mg/dl, Sodium (Na)-150 mEq/l, Potassium (K)- 4 mEq/l, Chloride (Cl)- 108 mEq/l, Phosphorus (P)- 18.4mg/dl). Routine urine analysis was normal. Ultrasound examination revealed distended uterine horns with echogenic material, measuring approximately 4.07 cm. However, cortico-medullary differentiation, size and contour of both the kidneys was within the normal limits suggesting pyometra with AKI. Initially to counter the AKI, IHD was undertaken along with rational treatment to extend the window of renal recovery as well as to undertake surgical intervention for ovario-hysterectomy. After surgery, dog was again referred to dialysis unit due to elevated uremic toxins. Blood gas analysis revealed metabolic acidosis with compensatory alkalosis. Again IHD was started immediately to lower down the blood creatinine level. After three sessions of hemodialysis animal’s renal function values (creatinine: 2.1mg/dl) and BUN: 27mg/dl) improved with resolved clinical signs. Discussion and Conclusion: This case report explains the management of complicated cases of pyometra with renal involvement using IHD concomitant with surgical intervention.